Anomalous origin of the coronary artery coursing between the great vessels presenting with a cardiovascular event (J-CONOMALY Registry). (25th April 2019) - Nagashima, Koichi; Hiro, Takafumi; Fukamachi, Daisuke; Okumura, Yasuo; Watanabe, Ichiro; Hirayama, Atsushi; Tanaka, Masashi; Tanaka, Tomofumi; Takamisawa, Itaru; Taguchi, Isao; Sato, Akira; Aonuma, Kazutaka; et al.
Abstract: Aims: Anomalous origin of the coronary artery (AOCA) with an inter-arterial course (IAC) between the great vessels poses a risk for a life-threatening cardiovascular event. We assessed, in a registry-based study, the clinical features, treatment strategies, and prognoses of life-threatening cardiovascular events ensuant to AOCA. Methods and results: Included were 65 AOCA patients (48 men/17 women, aged 41 ± 23 years) from 40 clinical centres who had experienced sudden cardiac arrest (SCA) ( n  = 30), acute myocardial infarction (AMI) ( n  = 5), angina ( n  = 23), or syncope ( n  = 7). The anomalous vessel was the right coronary artery in 72% of patients and left coronary artery in 28%; the ostium was slit-like in 42%. Coronary luminal narrowing ≥75% was absent in patients with SCA or syncope (86% and 57%, respectively), but occlusion or narrowing was seen in those with AMI (100%) or angina (52%). Age ≤40 years, male sex, sporting activity, absence of prodromal symptoms, acutely angled (≤30°) take-off from the aorta, and absence of luminal narrowing of the IAC segment were associated with SCA in this patient group. Coronary vasospasm was inducible in 12 of 17 patients without coronary narrowing. Management included surgical revascularization ( n  = 26) percutaneous coronary intervention ( n  = 9), and medical treatment ( n  = 26). Four SCA patients died while hospitalized; no others died during the median 5.0 (range, 1.8–7.0)-year follow-up period. Conclusions: In patients with AOCA, age ≤40 years, male sex, sporting activity, and an acute take-off angle appear to be risk factors for SCA. Appropriate management can be beneficial. Confirmation in a large-scale study is warranted.